Optimization for Ideological and Political Education of Undergraduates in the New Era - Ma, Qinjuan; Wang, Pingshui (IJRDO- Journal of Educational Research, 2019)
With the change of the times, the ideology of undergraduates in the new era is constantly changing. Based on the background of a complicated, variable domestic and overseas environment and the optimization for ideological and political education of undergraduates, several suggestions were proposed in the following to optimize the ideological and political education of undergraduates: (1) strengthening the leadership of local party committees and governments; (2) grasping the teaching of “two classrooms”; (3) focusing on "education"; (4) integrating into the practical life of undergraduates; (5) sticking to walking with "two legs" in counselors’ work.